Correction to: Therapeutic Effects of Photobiomodulation Therapy on Multiple Sclerosis by Regulating the Inflammatory Process and Controlling Immune Cell Activity: A Novel Promising Treatment Target - Vafaei-Nezhad, Saeed; Niknazar, Somayeh; Ali Asghar Payvandi, Ali Asghar; Shirazi Tehrani, Atefeh; Ahmady Roozbahany, Navid; Ahrabi, Behnaz; Abbaszadeh, Hojjat Allah; Darabi, Shahram (Journal of Lasers in Medical Sciences, 2025)
In the article titled “Therapeutic Effects of Photobiomodulation Therapy on Multiple Sclerosis by Regulating the Inflammatory Process and Controlling Immune Cell Activity: A Novel Promising Treatment Target” published in J Lasers Med Sci 2022;13:e32 (doi: 10.34172/jlms.2022.32), there was an error in the Ethical approval section. The ethics approval code was incorrectly reported as: “All protocols were confirmed by the Ethics Committee of Shahid Beheshti University of Medical Sciences (IR.SBMU.RETECH. REC.1400.009).” The correct ethics approval code is: IR.SBMU.REC.1400.009 The corrected sentence should read: “All protocols were confirmed by the Ethics Committee of Shahid Beheshti University of Medical Sciences (IR.SBMU.REC.1400.009 ).” This correction has now been updated in both the PDF and HTML versions of the article.